2020
DOI: 10.1111/dom.13973
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of herbal medicines for weight loss: A systematic review and meta‐analysis of randomized controlled trials

Abstract: Aim: To update the available evidence on the efficacy and safety of complementary medicines to assist in weight loss by conducting a systematic review and metaanalysis of herbal medicines for weight loss.Methods: Four electronic databases (Medline, Embase, CINAHL and Web of Science) were searched from inception until August 2018. A total of 54 randomized placebocontrolled trials of healthy overweight or obese adults were identified. Meta-analyses were conducted for herbal medicines with ≥4 studies available. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 91 publications
(159 reference statements)
0
62
1
4
Order By: Relevance
“…Another meta-analysis investigated the weight loss effects of complementary medicines and found that green tea-containing and garcinia-containing herbal medicines achieved 1.6 kg and 0.4 kg of weight loss, respectively. However, single preparations of each herbal extract were not associated with statistically significant changes [22]. Our study revealed that ephedrine-containing products were associated with around 2 kg of weight loss, which was greater than the extent of weight reduction associated with other herbal medicines but lower than that associated with weight loss drugs.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Another meta-analysis investigated the weight loss effects of complementary medicines and found that green tea-containing and garcinia-containing herbal medicines achieved 1.6 kg and 0.4 kg of weight loss, respectively. However, single preparations of each herbal extract were not associated with statistically significant changes [22]. Our study revealed that ephedrine-containing products were associated with around 2 kg of weight loss, which was greater than the extent of weight reduction associated with other herbal medicines but lower than that associated with weight loss drugs.…”
Section: Discussioncontrasting
confidence: 58%
“…Several systematic reviews and meta-analyses have evaluated the effectiveness of herbal medicines for weight loss [21][22][23]. However, most studies have assessed the shortterm efficacy of herbal medicines or have focused only on body weight and fat mass changes.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-adipogenic activity of P. vulgaris extract in the process of preadipocyte differentiation and its lipolytic effect were also identified (Castillo et al, 2019). Short-term (up to 12 weeks) supplementation with white beans has been shown to have no side effects (Maunder et al, 2020). However, frequent consumption of bean seeds can cause an allergic and toxic reaction.…”
Section: White Bean Seedsmentioning
confidence: 99%
“…Traditional East Asian medicine (TEAM) treatment for obesity management not only includes pharmacological (traditional herbal medicine) therapy, but also acupuncture, electro-acupuncture, pharmacopuncture, moxibustion, Qi-gong, cupping therapy, and other methods [9,20–24] . Herbal medicine using Ephedra sinica is a pivotal intervention that affects obesity-related clinical indicators such as weight, body fat mass, and abdominal circumference [25–27] …”
Section: Introductionmentioning
confidence: 99%